The Periplasmic Domain of the Ion-Conducting Stator of Bacterial Flagella Regulates Force Generation - Homma, Michio; Kojima, Seiji (Frontiers in Microbiology, 2022)
Bacterial flagellar stator is a unique ion-conducting membrane device composed of two kinds of proteins, A subunit and B subunit, that converts ion-motive force to rotational force. It becomes active only when incorporated into the flagellar motor and the periplasmic region is responsible to fix the stator by the region containing the peptidoglycan binding (PGB) motif. From the functional studies based on the crystal structures of the periplasmic region of stator (MotBC or PomBC), it has been revealed that the conformational change in the characteristic α-helix allows the stator to efficiently conduct ions and bind to the PG layer. The plug and the following linker region between the PGB and transmembrane (TM) region of B subunit function in regulating the ion conductance. In Vibrio, there are MotX and MotY, which are periplasmic proteins essential for the motor function, or FliL, which is the single TM protein to support the motor function. In this review, we'd like to link the functional and structural changes of stator units during a critical step for regulating the stator activity, thereby flagellar rotation.